Workplace stress: Intention to leave / Faizan Abd Jabar ...[et al.] - Abd Jabar, Faizan; Syed Wahid, Sharifah Norhuda; Abd Jabar, Mashita; Mohammad Ali, Halimah; Abu Bakar, Yusrina; Paino, Halil (2013)
Workplace stress becomes a serious employment issue that eats QW0' at profits and reduces efficiency. Stress affects people differently in which some m0' on extremely stressful lifestyles or struggle to cope with everyd0' life. Some even intend to leave their workplace. This study which was conducted among 36 UiTM Pahang lecturers revealed that there is a strong positive relationship between the workplace stress and intention to leave. This study also revealed that there is a significant difference in stress level between the young and senior lecturers. Surprisingly, these young lecturers are more stressful even though they just have been serving for less than five years as compared to senior lecturers. This is due to heavy workload and too much work to be done and doing others work make them feel stressful. It also indicates that senior lecturers can adapt to their workplace without having high level of stress. Hopefully this study can help the management team to overcome or reduce stress level especially among lecturers.